2018
DOI: 10.1007/s11999.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Is Legg-Calvé-Perthes Disease a Local Manifestation of a Systemic Condition?

Abstract: Level III, prognostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 64 publications
1
20
2
Order By: Relevance
“…In this nationwide cohort study, we found a slightly attenuated 90-day and overall mortality after THA in patients with previous LCPD, SCFE, or DDH, but the attenuation of 90-day mortality was not statistically significant. Despite a higher comorbidity and mortality risk in patients with LCPD and SCFE in general (Hailer and Nilsson 2014, Perry et al 2017, Hailer and Hailer 2018, Hailer 2020 we found no notable alterations of the mortality risks after THA in such patients, even after stratifying the analyses on the underlying pediatric hip diseases.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In this nationwide cohort study, we found a slightly attenuated 90-day and overall mortality after THA in patients with previous LCPD, SCFE, or DDH, but the attenuation of 90-day mortality was not statistically significant. Despite a higher comorbidity and mortality risk in patients with LCPD and SCFE in general (Hailer and Nilsson 2014, Perry et al 2017, Hailer and Hailer 2018, Hailer 2020 we found no notable alterations of the mortality risks after THA in such patients, even after stratifying the analyses on the underlying pediatric hip diseases.…”
Section: Discussioncontrasting
confidence: 61%
“…The long-term outcome and revision rates after THA in patients with previous pediatric hip disease have been studied (Thillemann et al 2008, Traina et al 2011), but 90-day mortality and overall mortality after THA in these patients have not yet been investigated. Comorbidities, such as attention deficit hyperactivity disorder (ADHD), depression, cardiovascular disease, hypothyroidism, obesity, and coagulation abnormalities are more common in patients with LCPD and SCFE (Hailer and Nilsson 2014, Perry et al 2017, Hailer and Hailer 2018, Hailer 2020). In addition, patients with LCPD and SCFE have a higher overall mortality than the general population (Hailer andNilsson 2014, Hailer 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a Swedish study of almost 4600 school children from the ages 7–9 years the overall prevalence of overweight was estimated at 17% and obesity at 3% [ 24 ]. An increased risk of obesity in patients with LCPD has been demonstrated in a population-based cohort study in Sweden [ 17 ]. However, obesity in that cohort was mostly diagnosed after the diagnosis of LCPD.…”
Section: Discussionmentioning
confidence: 99%
“…In some older studies children with LCPD have been described with low birth weight, skeletal retardation [ 13 ] and short body length [ 14 ]. In contrast, more recent studies have reported normal body habitus [ 15 ] or a rather high prevalence of overweight and obesity [ 16 ], including a higher risk of developing obesity later in life with a mean delay of 10 years [ 17 ]. Furthermore, childhood obesity is a risk factor for childhood hypertension [ 18 ] and is associated with metabolic syndrome, cardiovascular diseases, type 2 diabetes and its associated complications [ 19 ].…”
Section: Introductionmentioning
confidence: 99%